Portraying Women’s Agential Practices of Ideological Muslimah Community: A Passionate Approach to Islamist Politics - Maurisa Zinira; Wening Udasmoro; Muhammad Najib Azca (IJISH (International Journal of Islamic Studies and Humanities), 2023)
The issue of women and Islamism has been an increasing area of study to explore considering the number of women subscribing to the ideology continues to rise. Plenty of research has been conducted on this subject, but those available suggest that women were fragile victims of the ideology and were portrayed as passive actors who enact no agency. As we shall see, this research finds the opposite. Exploring the motivation and activism of the Ideological Muslimah community in Yogyakarta through a passionate politics approach, it discovers the agential practices of women in Islamist movement. Their motivation and engagement in Islamist politics demonstrate pluralities of women’s experiences and affirm the strong nexus of agency, emotion, and identity. By focusing on the agency and the play of emotion, this article aims to provide an alternate perspective to the burgeoning study of feminism and social movement, which has thus far been dominated by rational calculation of the action.